(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Agricultural innovation systems approach is necessary in the current demanding and complexnature of agriculture with the rising institutional heterogeneity in agricultural extension and advisoryservice delivery. Well co-ordinated, mutually beneficial cooperation among them may bring togetherideas, information as well as improved organizational culture and resources to work for the improvementof farmers. Multi-stakeholder collaborations and innovations are the avenues for future agriculturalextension and consulting services to reach needy farmers and others. In this study evaluation of theAgricultural Innovation Systems(AIS), features of AIS, capacity building for AIS, diagnostic assessmentof AIS, deficiencies of AIS.